2006
DOI: 10.1086/500554
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Standing Accretion Shock Instability with Neutrino Heating in Supernova Cores

Abstract: We have numerically studied the instability of the spherically symmetric standing accretion shock wave against non-spherical perturbations. We have in mind the application to the collapse-driven supernovae in the post bounce phase, where the prompt shock wave generated by core bounce is commonly stalled. We take an experimental stand point in this paper. Using spherically symmetric, completely steady, shocked accretion flows as unperturbed states, we have clearly observed both the linear growth and the subsequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
286
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 173 publications
(306 citation statements)
references
References 34 publications
19
286
1
Order By: Relevance
“…below the neutrinosphere of the electron neutrinos (Burrows 1987;Keil et al 1996;Buras et al 2006b;Dessart et al 2006); and (iii) convective overturn in the neutrino-heating layer between the gain radius and the stalled supernova shock (Herant et al 1994;Burrows et al 1995;Fryer & Warren 2002 as well as SASI activity (Blondin et al 2003;Blondin & Mezzacappa 2006;Ohnishi et al 2006;Scheck et al 2008). These regions can be identified for both 2D simulations in Fig.…”
Section: Hydrodynamic Instabilities and Shock Motionmentioning
confidence: 81%
“…below the neutrinosphere of the electron neutrinos (Burrows 1987;Keil et al 1996;Buras et al 2006b;Dessart et al 2006); and (iii) convective overturn in the neutrino-heating layer between the gain radius and the stalled supernova shock (Herant et al 1994;Burrows et al 1995;Fryer & Warren 2002 as well as SASI activity (Blondin et al 2003;Blondin & Mezzacappa 2006;Ohnishi et al 2006;Scheck et al 2008). These regions can be identified for both 2D simulations in Fig.…”
Section: Hydrodynamic Instabilities and Shock Motionmentioning
confidence: 81%
“…deformations, even in the absence of a negative entropy gradient. This instability was discovered numerically by Blondin et al (2003) and has been investigated further by Galletti & Foglizzo (2005), Blondin & Mezzacappa (2006), Ohnishi et al (2006), Foglizzo et al (2007), Laming (2007), Yamasaki & Yamada (2007), Scheck et al (2008), Endeve et al (2010, 2012), and Fernández et al (2014. Low mode, non-spherical shock deformations that result from this instability during the period after shock stagnation increase the mean shock radius and deflect postshock flows laterally, increasing the advection time of matter through the heating layer.…”
Section: Development Of Instabilities and Asphericitymentioning
confidence: 85%
“…For low-mass progenitors with O-NeMg core, the neutrino mechanism works successfully to explode in one-dimensional (1D) simulations because of the tenuous envelope (Kitaura et al 2006). For more massive progenitors with iron core, multi-dimensional (multi-D) effects such as neutrino-driven convection (e.g., Bethe 1990;Herant et al 1994;Burrows et al 1995;Janka & Müller 1996;Müller & Janka 1997) and the standing-accretion-shock-instability (SASI, Blondin et al 2003;Foglizzo et al 2006;Foglizzo et al 2007;Ohnishi et al 2006;Blondin & Mezzacappa 2007;Iwakami et al 2008;Iwakami et al 2009;Fernández & Thompson 2009;Hanke et al 2012; 2012; Couch 2013;Fernández et al 2014, see Foglizzo et al 2015 for a review) have been suggested to help the onset of the neutrino-driven explosion. Recently this has been confirmed by a number of self-consistent two-(2D) and three-dimensional (3D) simulations (e.g., Buras et al 2006;Ott et al 2008;Marek & Janka 2009;Bruenn et al 2013;Suwa et al 2010;Suwa et al 2014;Müller et al 2012a;Müller et al 2013;Takiwaki et al 2012;Takiwaki et al 2014;Hanke et al 2013;Dolence et al 2014;Bruenn et al 2014;Müller & Janka 2014, see Mezzacappa et al 2015Burrows 2013;Kotake et al 2012 for recent review)).…”
Section: Introductionmentioning
confidence: 99%